FROM TEACHING TO PRODUCTION: STRATEGIES FOR IMPROVING WRITING IN THE FFL CLASSROOM - Souad Benabbes; Abderrazak Benzouai (International Journal of Innovative Technologies in Social Science, 2025)
Writing plays a crucial role in secondary education, both as a communication tool and a means of learning, helping students assimilate content and become familiar with the writing requirements specific to each discipline. This study aims to assess writing teaching practices in French as a Foreign Language (FFL) classroom and identify teaching interventions to enhance learners’ written output. Through a questionnaire, teachers shared their perceptions of their students’ writing challenges and their strategies to address them. The analysis of the responses reveals a broad range of practices that focus on various stages of the writing process, with particular emphasis on revising texts.